Australia, China and the maritime 'rules-based international order': comparing the South China Sea and Timor Sea disputes. (6th November 2019) - Beeson, Mark; Chubb, Andrew
Abstract: Despite systemic internal and external differences, Australia and China have shown striking similarities in their pursuit of disputed maritime resource and jurisdictional claims. This high-stakes area of international politics is governed by a codified, globally accepted international legal regime (the United Nations Convention on the Law of the Sea), making it an important case for examining the relationship between states' foreign policies and the 'rules-based international order'. In the South China Sea, Beijing is haunted by the legacy of its strong geopolitically driven support for an expansive law of the sea regime in the 1970s. Strategic considerations also drove Australia's belated embrace of international legal processes in the Timor Sea in 2016. Before that, successive Australian governments had been as keen to pursue national maritime interests through bilateral negotiations as their Chinese counterparts. Australia's shift was enabled by pro-Timor domestic public opinion and a confluence of geographic and commercial circumstances not present in the South China Sea.